Evanescent wave interactions with nanoparticles on optical fiber modulate side emission of germicidal ultraviolet light. Issue 9 (20th August 2021) - Zhao, Zhe; Lanzarini-Lopes, Mariana; Westerhoff, Emma; Long, Xiangxing; Rho, Hojung; Bi, Yuqiang; Ling, Li; Westerhoff, Paul
Abstract : Silica nanoparticle coating on quartz optical fiber facilitates side-emission of germicidal ultraviolet light (UV-C), which shows promise for disinfection of contaminated air, water, and surfaces. Abstract : Silica nanoparticle coating on quartz optical fiber facilitates side-emission of germicidal ultraviolet light (UV-C), which shows promise for disinfection of contaminated air, water, and surfaces. However, the emitted light along the length of optical fibers decreases exponentially with distance from the LED light source, which makes designing applications more challenging and reduces overall useable length of optical fiber to disinfect water or surfaces. This work aims to develop an understanding of light interactions with the silica nanoparticles to allow more uniform side-emission of germicidal light along longer lengths of optical fibers. Two forms of light energy (refracted light and evanescent waves) are transmitted through optical fibers. The amount of side-emitted UV-C light is overwhelmingly controlled by the evanescent wave energy interacting with nanoparticles at distances from <2 to 100 nm from the surface of the optical fiber. Varying the separation distance enables up to ten-fold (10×) modulation in intensity of side-emitted UV-C light, demonstrated 1) experimentally through ionic-strength modifications during a manufacturing process, and 2) through first-principle models. These insights enabled fabrication of side-emitting optical fibers (SEOFs) with more uniform light emission along their entire length (>30 cm). The fundamental insights and experimental validation into light interactions with nanoparticles on SEOF surfaces, in conjunction with prior bacterial inactivation studies, enables use of UV-C light produced by light emitting diodes (LEDs) to mitigate biofilm formation on confined surfaces commonly found in water treatment, premise plumbing, and cooling systems.